A Case of Adult T-Cell Leukemia/Lymphoma Complicated with Bilateral Chylothorax. (17th February 2019) - Kako, Satoko; Joshita, Satoru; Matsuo, Akemi; Kawaguchi, Kenji; Umemura, Takeji; Tanaka, Eiji
Abstract : We present the case of a 74-year-old Japanese woman who presented with dyspnea, a palpable right breast mass, and swollen right axillary lymph node. Imaging studies revealed bilateral pleural effusion and systemic lymph adenopathy and pleural fluid study showed high levels of triglycerides. A right inguinal lymph node biopsy disclosed malignant lymphoma cells that were human T-cell leukemia virus type 1 (HTLV-1) provirus DNA-positive, a condition endemic to patient's birthplace, by the Southern blot hybridization method. She was diagnosed as having adult T-cell leukemia/lymphoma (ATL) with chylothorax. After commencing chemotherapy for ATL, her chylothorax disappeared and swollen lymph nodes reduced remarkably, indicating an association between the chylothorax and ATL. Bilateral chylothorax is a relatively rare condition associated with such nontraumatic causes as ATL. Clinicians should therefore bear chylothorax in mind when encountering patients with pleural effusion. A detailed medical history can also enable prompt diagnosis and appropriate treatment.